Xurt'an : the end of the world and other myths, songs, charms, and chants by the Northern Lacandones of Naha' - Cook, Suzanne, 1956- (Native literatures of the Americas., 2019)
"A comprehensive collection of Lacandon Maya oral literature, including narratives, myths, songs, and ritual speech"--